El concepto integral de la inspiración bíblica. De Dios “Espíritu” a la “Inspiración Bíblica” - Artola, Antonio María (Alpha omega, 2013)
The article seeks to produce an integral concept of biblical inspiration, based on a comparison of the seven different uses of the term ‘inspiration’: a Trinitarian use (the procession of the Holy Spirit) and six uses from the order of creation (creation, hominisation, incarnation, resurrection, forgiveness of sins, anointing). An integral concept can be found, starting from the fact that God is spirit (Jn. 4: 24) and arranging from this principle the other uses, from the primary concept which is that the Breath/ Spirit primordially means ‘air in movement’, which is then applied to all seven uses and, finally, to that of biblical inspiration. Sommario: L’articolo si propone di raggiungere un concetto globale di ispirazione biblica a partire dal confronto di sette diversi usi del termine ispirazione: un uso trinitario (la processione dello Spirito Santo) e sei dell’ordine creato (creazione, ominizzazione, incarnazione, risurrezione, perdono di peccati, unzione). Il concetto integrale si ottiene partendo dal fatto che Dio è Spirito (Giovanni 4:24) e organizzando da questo principio gli altri usi, vale a dire, dal concetto primario che il Soffio/Spirito significa in primo luogo “l’aria movimento”, che si applica a tutti e sette gli usi, e – per ultimo - all’ispirazione biblica.